A review of functional neuromodulation in humans using low-intensity transcranial focused ultrasound - Lee, Kyuheon; Park, Tae Young; Lee, Wonhye; Kim, Hyungmin (대한의용생체공학회, 2024)
Transcranial ultrasonic neuromodulation is a rapidly burgeoning field where low-intensity transcranial focused ultrasound (tFUS), with exquisite spatial resolution and deep tissue penetration, is used to non-invasively activate or suppress neural activity in specific brain regions. Over the past decade, there has been a rapid increase of tFUS neuromodulation studies in healthy humans and subjects with central nervous system (CNS) disease conditions, including a recent surge of clinical investigations in patients. This narrative review summarized the findings of human neuromodulation studies using either tFUS or unfocused transcranial ultrasound (TUS) reported from 2013 to 2023. The studies were categorized into two separate sections: healthy human research and clinical studies. A total of 42 healthy human investigations were reviewed as grouped by targeted brain regions, including various cortical, subcortical, and deep brain areas including the thalamus. For clinical research, a total of 22 articles were reviewed for each studied CNS disease condition, including chronic pain, disorder of consciousness, Alzheimer's disease, Parkinson's disease, depression, schizophrenia, anxiety disorders, substance use disorder, drug-resistant epilepsy, and stroke. Detailed information on subjects/cohorts, target brain regions, sonication parameters, outcome readouts, and stimulatory efficacies were tabulated for each study. In later sections, considerations for planning tFUS neuromodulation in humans were also concisely discussed. With an excellent safety profile to date, the rapid growth of human tFUS research underscores the increasing interest and recognition of its significant potential in the field of non-invasive brain stimulation (NIBS), offering theranostic potential for neurological and psychiatric disease conditions and neuroscientific tools for functional brain mapping.